Sami reindeer herders of the Lapland-Yukon Relief Expedition, probabaly at Woodland Park, 1898 - Wilse & Kirk (1898)
Probably one of the Sami reindeer herders of the Lapland-Yukon Relief Expedition, 1898 Caption on image: No. 573. Wilse & Kirk Photo, Seattle Stamped on verso: Wilse Scenic Fotografer, McDonald Blk. 811 2nd Ave. Seattle, Wash. Wilse 573 PH Coll 285.31 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number